The Nexus between Intercultural Communication and Peaceful Co-Existence in a Multi-Cultural State - Olumide Samuel Ogunjobi (Britain International for Academic Research (BIAR-Publisher), 2022)
Different societies and cultures have varying values and norms in interpersonal and intergroup interaction. Where the communication is intracultural, the norms hardly constitute any hindrances, but in intercultural communication, the varying values could pose serious challenges. Along with the rapid globalization of the era, the public is increasingly paying attention to intercultural communication as an important component of success, both in life and at work. It is general knowledge that human beings cannot live without communication and due to the influence of globalization; communication is no longer confined solely to a community and national level but also on an international scale. Thus, intercultural communication is now more important than it ever was in every facet of society. Yet the effective intercultural communication needed for the aforementioned success is difficult to achieve. The paper adopted the library research method used to interrogate literature by getting data from secondary sources which will provide valuable useful materials for the study. The paper also conceptually discusses intercultural communication, obstacles, and possible solutions to these challenges in a multi-cultural state. Finding from the study suggests that working intercultural communication skill cannot only assist in eliminating communication issues like conflicts and misunderstanding but also promote a mutually beneficial relationship with parties involved in the communication process.